Communicative Competence of Early Childhood Islamic Education Students: The Synergy between Islamic Pedagogy and Modern Communication Studies - Kabul Suprayitno; Fauziah Hassan; Sanjaka Yekti; Ahmadi Ahmadi (Institut Agama Islam Negeri Parepare, 2026)
Tier 4- Non-Indexed Publication